Studies on the mechanisms underlying activity in the subthalamic nucleus-globus pallidus network - Magill, P; Magill, Peter (2001)
The reciprocally-connected network of neurons of the subthalamic nucleus (STN) and globus pallidus (GP) plays a pivotal role in basal ganglia function and dysfunction. A series of in vivo and in vitro electrophysiological studies were performed in order to elucidate the mechanisms underlying activity in the STN-GP network. To characterise the relationship of activity in the normal STN-GP network to activity in the cerebral cortex, the principal excitatory afferent of the basal ganglia, single and multiple unit activity in STN and/or GP were recorded together with cortical electroencephalogram in anaesthetised rats during various states of cortical activation and inactivation. The data suggested that: (1) the rate and pattern of firing of STN and GP neurons are intimately related to coincident cortical activity and hence, the sleep-wake cycle; (2) oscillatory activity in the STN-GP network in health and disease may be driven by the cortex; and (3) activity of the network is regulated in space and time in a complex manner. To provide insight as to whether the relationship between the STN-GP network and the cortex is altered in Parkinson's disease (PD), a similar study was undertaken using a well established model of experimental PD, the unilateral 6-hydroxydopamine-lesioned rat. The results indicated that: (1) activity in the STN-GP network is dramatically altered by the chronic loss of dopamine from the forebrain; (2) the impact of the cortex on the network is modulated by dopamine and thus, pathological oscillatory activity in the basal ganglia in PD may be caused by the inappropriate processing of rhythmic cortical input; (3) the classical indirect pathway is abnormally augmented during activation of the parkinsonian brain; and (4) the relative contributions of firing rate and pattern to information coding in the STN-GP network and the basal ganglia is related to the state of cortical activation. To examine the dynamics of GABAergic inhibition in the STN and to test whether GABAA receptor-mediated synaptic input from the GP could generate rebound burst-firing in STN neurons, a phenomenon which may contribute to normal and abnormal activity in the STN-GP network, the equilibrium potential of GABAAreceptor-mediated current, the reversal potential of GABAA receptor-mediated inhibitory post-synaptic potentials, and the degree of membrane hyperpolarisation required for rebound burst-firing were determined using perforated patch-clamp recordings in vitro. An extension of this study investigated the responses of STN neurons to different patterns of inhibitory synaptic input. The findings implied that: (1) active chloride homeostasis ensures a large net driving force for GABAA receptor-mediated events in STN neurons; (2) asynchronous and irregular inhibitory input from the GP has a profound influence on activity in the STN; and (3) synchronous, bursting activity in the parkinsonian GP could contribute to pathological oscillatory activity in the BG by generating rebound burst-firing in STN neurons. In conclusion, the three studies have identified a number of key mechanisms underlying the activity of the STN-GP network. The importance of the corticosubthalamic projection in driving the activity of the STN-GP network has been established, suggesting that the STN should not be viewed as a simple relay station along the indirect pathway, but rather as a second important entry point for cortical information in the basal ganglia. Furthermore, the activity of STN and GP neurons was coupled, albeit to varying degrees, and thus, the reciprocal connections between these neurons are of great importance in shaping the activity of the network.